Peran Guru dalam Menangani Siswa yang Kecanduan dengan Game Online Di Sekolah Menengah Atas Negeri 3 Gorontalo Utara, Kecamatan Atinggola, Kabupaten Gorontalo Utara - Kamuli, Sukarman; Lukum, Roni; Tialo, Sahril Anwar (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
At State Senior High School 3 North Gorontalo, Atinggola District, North Gorontalo Regency, Gorontalo Province, the tendency is for students to forget the culture of their own nation. The culture of playing online games requires a more teacher role for these students. Based on the problems above, the researchers conducted outreach to students at State High School 3 Gorontalo Utara, Atinggola District, North Gorontalo Regency with the aim of (1) Instilling the values of national character to students at State High School 3 North Gorontalo , Atinggola District, North Gorontalo Regency (2) Fostering a spirit of discipline in all students so that they come to school more disciplined (3) getting used to good things in each student. The problem that occurs among students is the inability of students to stem the influence of online games which results in reduced student motivation and enthusiasm for learning. After carrying out the Mentoring and Socialization activities for students, we plan to do a mapping to find out how successful the teacher is in guiding his students.